Penggunaan Media Digital Meningkatkan Keterampilan Berbicara Siswa - Diyah Mahmawati; Andika Pratama Setiawan; Syafi’atul Mubayyinah (PPPM STIT MIFTAHUL MIDAD, 2025)
This study aims to examine the effect of digital media use on improving student learning outcomes at STIT Miftahul Midad Lumajang. A quantitative research approach with a quasi-experimental design was employed. The population consisted of 30 students from a single class, who were given both pre-tests and post-tests to assess their learning performance before and after the integration of digital media in the learning process. The findings revealed a significant improvement in students’ learning outcomes following the implementation of digital media. These results suggest that digital media can serve as an effective tool to enhance learning quality in higher education, particularly in promoting better understanding of the material and increasing student engagement in the classroom.